Short communication: miRNA122 interrogation via PCR-Free method to track liver recovery - Antonio Marín-Romero; Daniel E. Di Zeo-Sánchez; Mavys Tabraue-Chávez; Marina Villanueva-Paz; Jose M. Pinazo-Bandera; Judith Sanabria-Cabrera; Miren García-Cortés; Juan J. Díaz-Mochón; M. Isabel Lucena; Raúl J. Andrade; Camilla Stephens; Salvatore Pernagallo (PLoS ONE, 2025)
There is currently a need to investigate new biomarkers of acute liver injury (ALI) that are highly specific to the liver and capable of detecting early-stage liver damage. In this regard, circulating microRNAs (miRNAs), particularly microRNA122 (miRNA122), have recently been proposed as promising new candidate biomarkers. However, the quantification of miRNAs is not a standardized technique and presents several challenges that hinder its routine use. The aim of this work is to validate the innovative Dynamic Chemical Labeling (DCL) PCR-Free technology for its ability to detect miRNA122 in patient samples using Luminex xMAP platforms. The DCL PCR-Free technology was used to directly measure and monitor miRNA122 levels in serum samples from patients with ALI. Patients were monitored throughout the recovery process from liver injury, from the time of detection and for up to 30 days afterwards, with follow-up over three separate visits. The results demonstrate the robustness of the method, with sensitivity of 3.36% and precision of 99.80%, and show a high correlation between miRNA122 and traditional liver injury markers such as ALT (r = 0.8150, p = 0.0001), AST (r = 0.7895, p = 0.0002) and TBL (r = 0.2646, p = 0.3406) throughout the ALI recovery process. In conclusion, measuring miRNA122 levels using the DCL PCR-Free method provides a distinctive approach, not only for diagnosing ALI patients but also for effectively monitoring disease progression, tracking liver recovery, and evaluating treatment effectiveness.